The effect of novel chromosome position and variable dose on the genetic behavior of the Responder (Rsp) element of the Segregation distorter (SD) system of Drosophila melanogaster. - Lyttle, T.W. (Genetics, 1989)
In the Segregation distorter (SD) system of meiotic drive, a minimum of two trans-acting elements [Sd and E(SD)] act in concert to cause a certain probability of dysfunction for sperm carrying a sensitive allele at the Responder (Rsp) target locus. By employing a number of insertional translocations of autosomal material into the long arm of the Y chromosome, Rsp can be mapped as the most proximal locus in the 2R heterochromatin as defined both by cytology and lethal complementation tests. Several of these insertional translocations result in the transposition of Rsp to the Y chromosome, where its sensitivity remains virtually unaltered. This argues that Rsp is separable from the second chromosome centromere, that its behavior does not depend on its gross chromosomal position, and that meiotic pairing of the chromosomes carrying the various SD elements is not a prerequisite for sperm dysfunction. Several other translocations apparently leave both resulting chromosomes at least partially sensitive to SD action, suggesting that Rsp is a large subdivisible genetic element. This view is compatible with observations published elsewhere that suggest that Rsp is a cytologically large region of highly repetitive AT-rich DNA. The availability of Y-linked copies of Rsp also allows the construction of SD males carrying two independently segregating Rsp alleles; this in turn allows the production of sperm with zero, one or two Rsp copies from the same male. Examination of the relative recovery proportions of progeny arising from these gametes suggests that sperm with two Rsp copies survive at much lower frequencies than would be predicted if each Rsp acted independently in causing sperm dysfunction. Possible explanations for such behavior are discussed.